1976
DOI: 10.1111/j.1399-3054.1976.tb04430.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Factors Affecting Palmelloid‐Forming Activity of Chloroplatinic Acid on Chlamydomonas eugametos

Abstract: In order to elucidate the physiological mechanism of palmelloid formation of the unicellular green alga Chlamydomonas eugametos by chloroplatinic acid, the factors causing inhibition of the palmelloid formation were studied in various media. Chloroplatinic acid lost its palmelloid‐forming effect in the presence of nitrite ion and amines having a second functional group. Nitrate, potassium, and sodium ions and monofunctional amines were without influence on the effect of chloroplatinic acid. These results indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 11 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…Variations observed in the FSC signal detected by FCM in the C. eugametos cultures treated with 0.60 μM paraquat ( Fig. 5) could be related to palmeloid colony formation, since several factors can induce the formation of these structures in the genus Chlamydomonas ( Nakamura et al, 1976 andOlsen et al, 1983). This palmeloid structure appears probably due to the incapacity to finish cell division, as well as failures of regulation of cellular volume as a consequence of the high levels of oxidative radicals formed.…”
Section: Discussionmentioning
confidence: 96%
“…Variations observed in the FSC signal detected by FCM in the C. eugametos cultures treated with 0.60 μM paraquat ( Fig. 5) could be related to palmeloid colony formation, since several factors can induce the formation of these structures in the genus Chlamydomonas ( Nakamura et al, 1976 andOlsen et al, 1983). This palmeloid structure appears probably due to the incapacity to finish cell division, as well as failures of regulation of cellular volume as a consequence of the high levels of oxidative radicals formed.…”
Section: Discussionmentioning
confidence: 96%
“…The increase of cellular dry weight at the highest concentrations of paraquat assayed is related with the inhibitory effect on growth; in these cultures, cells formed palmelloid colonies (clusters of nonflagellated cells closed in a common wall), observed by light microscopy. Several factors can induce the formation of these structures in Chlamydomonas (Iwasa and Murakami 1968;1969;Nakamura et al 1976;Olsen et al 1983). Palmelloid colonies became attached to the walls of the culture vessel and subsequently showed a much slower growth rate than nonpalmelloid vegetative cells.…”
Section: Lipids and Pigments Contentmentioning
confidence: 99%
“…Comparative genomic studies have highlighted that the evolution of multicellularity involves the co-option of genes regulating cell replication in green algae 44,45 . Research on unicellular algae has also shown that the cell-replication cycle can be arrested when mother cells divide mitotically into four daughter cells (palmelloids) in the face of various environmental stressors and when zygospores cannot form, for example, when nitrogen is not limited 13,46 . It is therefore possible that environmental conditions that induce cellular stress alter cell-replication cycles, causing multicellular groups to form as a by-product.…”
Section: Multicellular Groups Form Via the Retention Of Daughter Cellsmentioning
confidence: 99%